Peran Kepemimpinan Dalam Membangun Mengembangkan Manajemen Sumber Daya Manusia Di Sekolah - Mahsunah Mahsunah; Aditya Putra Ayuni; Andyni Loisalina Hidayat; Arida UlulAzmi (CV. ITTC INDONESIA, 2024)
This research discusses the role of leadership in the development and management of human resources (HR) in schools. Human resources are an important element that determines the effectiveness and productivity of an educational institution. This research aims to explore the role of leaders in managing human resources, especially regarding the challenges faced, the leadership strategies implemented, and their impact on improving the quality of teaching staff. The research method applied is literature study, by collecting information from a variety of relevant sources, such as books, journals and previous research. The research results show that quality leadership plays a significant role in creating a productive work environment, increasing the motivation of teaching staff, and optimizing the use of school resources. The conclusions of this research emphasize the importance of an adaptive and empowering leadership style to improve the overall performance of educational institutions.